EFEKTIFITAS MODEL PEMBELAJARAN DIRRECT INSTRUCTION DENGAN STRATEGI MOTIVASI ARCS PADA MATERI GRAPH - Kuswardi, Yemi; Kurniawati, Ira; Sutopo, Sutopo (Journal of Mathematics and Mathematics Education, 2011)
ABSTRACT Graph materials contains declarative knowledge and procedural knowledge. In Graph subject included declarative knowledge is the graph terminology while those included procedural knowledge is how to determine the settlement of problems by using the algorithm methods associated with Graph. Dirrect instruction that relies on principles of behavioral and social learning theory, has been specifically designed to support students learning processes associated with procedural knowledge and declarative knowledge is well structured and can be taught with the pattern of activity that gradually, step by step. ARSC motivation strategies (Attention, Relevance, Confidence, Satisfaction) is a strategy that can increase the motivation on learning materials and learning activities of students. Application of direct instruction model with ARCS motivational strategies is one solution to resolve the issue. The purpose of this study was to determine whether the aplication of direct istruction model using ARCS strategy on graph materials subject (1) the mastery learning is achieved, (2) students learning activities are effective, (3) students responses are positive, and (4) the effectiveness of model is reached. This research is a qualitative descriptive research. The subjects of this research are students who take Discrete Mathematics course in Educational Mathematics Program, Department of Educational Mathematics and Science, FKIP, Sebelas Maret University Surakarta. The results is (1) mastery learning achieved, (2) learning activities are effective, (3) students response considered positive, (4) the effectiveness of interactive learning on graph is achieved. Keywords: Dirrect Instruction Model, Motivation Strategies ARCS, Discrete Mathematics, Graph